Genomic Signatures of Positive Selection and Local Adaptation in Ethiopian Sheep Populations - Demissie, B. E.; Tarekegn, G. M.; Dadi, H.; Edea, Z.; Woldesemayat, A. A.; Kim, K-S; Girma, S.; Seyoum, T.; Melaku, K.; Keskes, S. (Tropical Animal Science Journal, 2025)
Domestic sheep (Ovis aries) have adapted to diverse ecological regions and exhibit various phenotypic traits through long-term natural and artificial selection. Indigenous sheep populations, in particular, have developed valuable traits such as disease resistance, heat tolerance, and resilience to harsh environments. Understanding the genetic mechanisms underlying these adaptive traits is crucial for enhancing, sustainably utilizing, and conserving sheep genetic resources. In this study, we aimed to assess genomic selection among five Ethiopian indigenous sheep populations sampled from various ecological regions. Whole blood samples were randomly collected from 48 sheep representing two populations (Semien and Selale) from different ecological regions and genotyped using the Ovine 50K SNP BeadChip. Genotype data from three Ethiopian sheep populations was additionally included in the analyses. Fixation index (FST) and cross-population extended haplotype homozygosity (XPEHH) methods were used to detect signatures of positive selection. Functional analysis revealed genes related to plateau adaptation, immune response, and tail fat formation. Our study identified potential genes associated with alpine and sub-alpine adaptation, including GABRG3, SYT1, TGFBR3, ITPR2, KCNMB2, and ATP1A3. Candidate genes linked with wet highland adaptation, including GNB1, HDAC9, IGFBP6, JAKMIP1, PAK2, and EXOC4, were also detected as under selection. The BMP2 gene, known for its fundamental role in sheep adipose tissue, emerged as a positional candidate gene for tail fat formation. This study offers novel insight into genomic adaptation to alpine, sub-alpine, and wet highland ecological regions in sheep and provides a valuable resource for further investigation. Moreover, it contributes worthwhile information for sustainable conservation and utilization, and lays the groundwork for future research into the genetic mechanisms behind sheep adaptability to diverse ecological regions.